Targeting the tumor microenvironment: focus on Angiogenesis - Fan, Fengjuan; Schimming, Alexander; Jäger, Dirk; Podar, Klaus (Journal of oncology, 2012)
Tumorigenesis is a complex multistep process involving not only genetic and epigenetic changes in the tumor cell but also selective supportive conditions of the deregulated tumor microenvironment. One key compartment of the microenvironment is the vascular niche. The role of angiogenesis in solid tumors but also in hematologic malignancies is now well established. Research on angiogenesis in general, and vascular endothelial growth factor in particular, is a major focus in biomedicine and has led to the clinical approval of several antiangiogenic agents including thalidomide, bevacizumab, sorafenib, sunitinib, pazopanib, temesirolimus, and everolimus. Indeed, antiangiogenic agents have significantly changed treatment strategies in solid tumors (colorectal cancer, renal cell carcinoma, and breast cancer) and multiple myeloma. Here we illustrate important aspects in the interrelationship between tumor cells and the microenvironment leading to tumor progression, with focus on angiogenesis, and summarize derived targeted therapies.